INCREASING THE STUDENTS’ MOTIVATION AND LEARNING OUTCOMES THROUGH VARIED DEMONSTRATION METHOD FOR SOCIAL SCIENCE SUBJECT AT ELEMENTARY SCHOOL - Sri Suwartini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to increase the students’ motivation and learning outcomes on the material of documents and valuable objects at grade II elementary school in the academic year 2017/2018. The research was conducted by involving 13 children as the objects. The type of this research was classroom action research which was carried out in two cycles. In the first cycle, the varied demonstration method was carried out classically and in the second cycle, it was carried out in groups. Each cycle consisted of four stages: planning the action, implementing the action as planned, observing the results of the action, and reflecting on the implementation of the action. The tools for data collection were the document of students’ grade list, observation sheets, and question sheets since the data were collected using documentation, observation, and test. The results showed that the varied demonstration method improved the students’ learning outcomes in social science subject especially on the material of documents and valuable objects at grade II in the academic year 2017/2018. This was proved by an increase with a success rate of 57.80% in cycle I, and 93.33% in cycle II.